Phase-segregated NiPx@FePyOz core@shell nanoparticles: ready-to-use nanocatalysts for electro- and photo-catalytic water oxidation through in situ activation by structural transformation and spontaneous ligand removal. Issue 21 (10th May 2018) - Saruyama, Masaki; Kim, Sunwon; Nishino, Toshio; Sakamoto, Masanori; Haruta, Mitsutaka; Kurata, Hiroki; Akiyama, Seiji; Yamada, Taro; Domen, Kazunari; Teranishi, Toshiharu
Abstract : The phase-segregated NiP x @FeP y O z core@shell NPs act as a colloidally stable, ready-to-use, and excellent OER active transition metal phosphide-based catalyst. Abstract : The high overpotential of the oxygen evolution reaction is a critical issue to be overcome to realize efficient overall water splitting and enable hydrogen generation powered by sunlight. Homogeneous and stable nanoparticles (NPs) dispersed in solvents are useful as both electrocatalysts and cocatalysts of photocatalysts for the electro- and photo-catalytic oxygen evolution reaction, respectively, through their adsorption on various electrode substrates. Here, phase-segregated NiP x @FeP y O z core@shell NPs are selectively synthesized by the reaction of Fe(CO)5 with amorphous NiP x seed-NPs. The NiP x @FeP y O z NPs on conductive substrates exhibit higher electrocatalytic activity in the oxygen evolution reaction than those of other metal phosphide-based catalysts. The NiP x @FeP y O z NPs can also be used as a cocatalyst of an anodic BiVO4 photocatalyst to boost the photocatalytic water oxidation reaction. The excellent catalytic activity and high stability of the NiP x @FeP y O z NPs without any post-treatments are derived from in situ activation through both the structural transformation of NiP x @FeP y O z into mixed hydroxide species, (Ni, Fe)O x H y, and the spontaneous removal of the insulating organic ligands from NPs to form a smooth and robust (Ni, Fe)O x H y /substrate heterointerface during the oxygen evolution reaction.